DNA N(6)-Methyladenine: a new epigenetic mark in eukaryotes? - Luo, Guan-Zheng (Nat Rev Mol Cell Biol, 2015)
DNA N(6)-adenine methylation (6mA) in prokaryotes functions primarily in the host defense system. The prevalence and significance of this modification in eukaryotes has been unclear until recently. Here we discuss recent publications documenting the presence of 6mA in Chlamydomonas reinhardtii, Drosophila melanogaster and Caenorhabditis elegans, consider possible roles for this DNA modification in regulating transcription, transposable elements and trans-generational epigenetic inheritance, and propose 6mA as a new epigenetic mark in eukaryotes.